Biomedical Monitoring, IoT in Hospital Industry: Focusing on Solidification of Data Security and Privacy of Patients - Bhupinder Singh (International Journal of Mobile Computing Technology, 2024)
Improving the security of internet of things (IoT) communication and ensuring the safety of intelligent healthcare systems are significant objectives for biomedical microelectromechanical systems (BioMEMS). BioMEMS, which are at the cusp of healthcare and cutting-edge technology, propel the creation of tailored monitoring, therapeutics, and diagnostics. But because of the intricate security and privacy issues that come with IoT connections in smart healthcare ecosystems, a careful analysis is required. Various security solutions are explored, including robust authentication processes, data encryption, resistant design against attacks, and continuous monitoring mechanisms, all tailored to bolster BioMEMS against evolving threats in smart healthcare environments. This paper underscores the significance of ethical and regulatory considerations, advocating for patient autonomy, data confidentiality, and equitable healthcare access in the context of IoT communication security This paper addresses risks such as cyberattacks, data manipulation, and communication interception by doing a thorough examination of the complex security landscape surrounding IoT communications in BioMEMS.
Keywords: Biomedical monitoring; Internet of things (IoT); Privacy; data; hospital industry; patient information